Learning from Place: A Return to Traditional Mushkegowuk Ways of Knowing - Restoule, Jean-Paul; Gruner, Sheila; Metatawabin, Edmund (Canadian Journal of Education/Revue canadienne de l'éducation, 2013)
This paper details a research project dedicated to honouring Mushkegowuk Creeconcepts of land, environment and life in Fort Albany First Nation. Communityyouth interviewed local Elders to produce an audio documentary about therelations of the people to their traditional territory. These interactions evolved intoa 10-day river trip with youth, adult and elder participants traveling together ontheir traditional waters and lands learning about the meaning of paquataskamik,the Cree word used for traditional territory, all of the environment, nature, andeverything it contains. Bringing generations of community members together onthe land led to reclamation of culture and indigenous knowledge and built greatercommunity resistance to external forms of economic exploitation anddevelopment.